Political life after ethnic war - Sarah Zukerman Daly (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2025)
In post-war elections a large number of citizens vote for political parties with deep roots in the violent organizations of the past. However, despite the prevalence of rebel, militia, and military successor parties, their success varies dramatically. This study explores the correlates of civil war belligerent party performance in contexts emerging from ethnic wars fought over government control and over territory. It seeks to understand how parties with coercive legacies seek votes and why, in turn, citizens go to the polls and elect these parties to political office following these different types of conflicts. The study embeds illustrative case studies of ethnic wars within an original cross-national database of founding post-war elections between 1970 and 2015.
Keywords: 330; post-war elections; ethnic war; case studies; cross-national data; violent organizations; parties